Plan de exportación de incienso artesanal Bursera Graveolens Palo Santo al mercado de Estados Unidos - Bueno Vera, Adriana Alejandra (2019)
The project titled Bursera Graveolens Craft Incense (Palo Santo) to the market Los Angeles - United States, was justified due to the opportunity offered by the market for the export of this product. Ecuador, thanks to the various artisanal products that it has, is in great demand in industrialized countries, such as the United States, and this product is aimed at the pharmaceutical and cosmetic and beauty industries where inputs such as: essential oils, creams are used, giving use for preserving its aroma. The micro company of Mr. JULIO LUIS MALTA DIVIASSI with commercial name HOLY WOOD EXPORT, is one of the distributors nationwide in marketing this type of product, however, over the years its sales have declined on a small scale. Therefore, a way to promote the commercialization of artisanal incense, the present study is developed through the methodology of the descriptive method and the mixed approach, when applying surveys to potential buyers, it results in the high export potential of the product, the interest in the purchase and the opportunities of consumption since to the country that is tried to send exist many Latin Americans who know of the uses and benefits of this type of wood…….